Cell types and morphogenesis in the mammary gland. - Dulbecco, R (1982)
Cell types present in the mammary gland and their evolution were studied by labeling female rats with radioactive thymidine at various phases of the estrus cycle. The results suggest that the stem cells for mammary development are present in the terminal end buds and that they generate a lineage for lumenal cells and possibly a distinct one for myoepithelial cells. Growth and differentiation are controlled by both hormones and local factors.